Forging Professional Identity: Navigating Conflicting Curricular Principles in on-the-Job Principal Training - Chamo, Nurit (Journal of Posthumanism, 2025)
This article examines the complex process of forging teacher professional identity (TPI) within the context of on-the-job principal training programs, where competing curricular principles often create tension between national policy mandates and the realities of school-level practice. Using an auto ethnographic approach, the author reflects on their dual role as both academic faculty member and program facilitator to uncover how professional identity is shaped, negotiated, and sometimes challenged through this dynamic mediation. The study highlights how the formal curriculum, grounded in managerial and accountability-driven frameworks, often clashes with the informal curriculum that emerges from lived experiences in schools. The findings illuminate the ongoing struggle to prioritize identity development within a programmatic and cultural context that often favors technical skill-building. Faculty members occupy a contested space, navigating external mandates, collegial disagreements, and evolving conceptions of leadership. The academic director’s role is both meditational and visionary, working to embed a deeper sense of professional purpose into the curriculum. Through incremental adaptations and narrative advocacy, the program carves out room for leadership as reflective, relational, and anchored in identity. Findings contribute to broader discussions on educational leadership preparation, curriculum coherence, and identity formation in the face of structural contradictions.